Effect of cinnamon essential oils addition in the sensory attributes of dark chocolate - MUHAMMAD ISA DWIJATMOKOa; DANAR PRASEPTIANGGA; DIMAS RAHADIAN AJI MUHAMMAD (Nusantara Bioscience, 2016)
Abstract. Dwijatmoko MI, Praseptiangga D, Muhammad DRA. 2016. Effect of cinnamon essential oils addition in the sensory attributes of dark chocolate. Nusantara Bioscience 8: 301-305. Chocolate is one of the most popular confectionery products in the world. The increasing demand for healthy foods has led to rapid growth in innovative healthy chocolate. Cinnamon (Cinnamomum burmanii) has been widely used as flavoring agent in the food product as well as has been proven to have benefit for human well-being. This study aims to investigate the effect of cinnamon essential oils added in dark chocolate on consumer acceptance. A hedonic test using untrained panelists was performed in this research. The result showed that the presence of the cinnamon essential oils changed significantly on the panelist acceptability to the chocolate.